European Psychiatric Association guidance on psychotherapy in chronic depression across Europe - Jobst-Heel, Andrea; Brakemeier, E.-L.; Buchheim, A.; Caspar, F.; Cuijpers, P.; Ebmeier, K. P.; Falkai, P.; Der, Gaag R. Jan van; Gaebel, W.; Herpertz, Sabine; Kurimay, T.; Sabaß, L.; et al. (European psychiatry, 2020)
PurposePatients with chronic depression (CD) by definition respond less well to standard forms of psychotherapy and are more likely to be high utilizers of psychiatric resources. Therefore, the aim of this guidance paper is to provide a comprehensive overview of current psychotherapy for CD. The evidence of efficacy is critically reviewed and recommendations for clinical applications and research are given.MethodsWe performed a systematic literature search to identify studies on psychotherapy in CD, evaluated the retrieved documents and developed evidence tables and recommendations through a consensus process among experts and stakeholders.ResultsWe developed 5 recommendations which may help providers to select psychotherapeutic treatment options for this patient group. The EPA considers both psychotherapy and pharmacotherapy to be effective in CD and recommends both approaches. The best effect is achieved by combined treatment with psychotherapy and pharmacotherapy, which should therefore be the treatment of choice. The EPA recommends psychotherapy with an interpersonal focus (e.g. the Cognitive Behavioural Analysis System of Psychotherapy [CBASP]) for the treatment of CD and a personalized approach based on the patient's preferences.DiscussionThe DSM-5 nomenclature of persistent depressive disorder (PDD), which includes CD subtypes, has been an important step towards a more differentiated treatment and understanding of these complex affective disorders. Apart from dysthymia, ICD-10 still does not provide a separate entity for a chronic course of depression. The differences between patients with acute episodic depression and those with CD need to be considered in the planning of treatment. Specific psychotherapeutic treatment options are recommended for patients with CD.ConclusionPatients with chronic forms of depression should be offered tailored psychotherapeutic treatments that address their specific needs and deficits. Combination treatment with psychotherapy and pharmacotherapy is the first-line treatment recommended for CD. More research is needed to develop more effective treatments for CD, especially in the longer term, and to identify which patients benefit from which treatment algorithm.